123k views
5 votes
Which of the following represents the solutions x^2 -4x+12=6x-2

User Perdixo
by
5.5k points

1 Answer

4 votes

Given the equation:


x^2-4x+12=6x-2

Let's find the solution to the given equation.

Move all terms to the left and equate to zero.

Ad 2 and subtract 6x to both sides:


\begin{gathered} x^2-4x-6x+12+2=6x-6x-2+2_{} \\ \\ x^2-10x+14=0 \end{gathered}

Let's solve usingbthe quadratic formula:


x=\frac{-b^{}\pm\sqrt[]{b^2-4ax}}{2a}

Apply the general formula to find the values of a, b, and c:


\begin{gathered} ax^2+bx+c=0 \\ \\ x^2-10x+14=0 \end{gathered}

Thus, we have:

a = 1

b = -10

c = 14

Substitute the values into the quadratic formula:


\begin{gathered} x=\frac{-(-10)\pm\sqrt[]{-10^2+4(1)(14)}}{2(1)} \\ \\ x=\frac{10\pm\sqrt[]{100+56_{}}}{2} \\ \\ x=\frac{10\pm\sqrt[]{44}}{2} \\ \\ x=\frac{10\pm\sqrt[]{4\ast11}}{2} \\ \\ x=\frac{10\pm\sqrt[]{2^2\ast11}}{2} \\ \\ x=\frac{10\pm2\sqrt[]{11}}{2} \\ \\ x=5\pm\sqrt[]{11} \end{gathered}

Solving further:


\begin{gathered} x=5+\sqrt[]{11},\text{ 5-}\sqrt[]{11} \\ \\ x=5+3.317,\text{ 5-3.31}7 \\ \\ x=8.317,\text{ 1.683} \end{gathered}

Therefore, the solutions are:

x = 8.317, 1.683

ANSWER:

8.137 and 1.683

User VirtualVDX
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.